Update of the European paediatric respiratory medicine syllabus. Issue 3 (September 2019) - Primhak, Robert; Tabin, Nathalie; Beydon, Nicole; Bhatt, Jayesh; Eber, Ernst; Hammer, Jürg; Martinez-Gimeno, Antonio; Midulla, Fabio; Nenna, Raffaella; Paton, James; Ross Russell, Robert
The 10-year-old European syllabus for paediatric respiratory medicine (PRM; also known as paediatric pulmonology) was updated by a consensus-based method using an expert task force for redrafting, and a subsequent Delphi process to achieve consensus. There was a high degree of consensus for the final syllabus, which has been streamlined and made more relevant to current practice. All modules are now mandatory apart from the undertaking of research projects, which is optional. Although there are still a number of countries in Europe which do not recognise PRM as a separate subspecialty, there are paediatric respiratory physicians practising in every country in Europe, and a current and harmonised European syllabus in the subspecialty remains important for defining the training and areas of practice of PRM practitioners. The European syllabus for paediatric respiratory medicine has been updated by a task force in conjunction with the ERS Paediatric Assembly and designated national experts. It has several new modules, and only one optional module remains. http://bit.ly/2KB9wcy